2023
DOI: 10.3390/antiox12050988
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Mechanisms of Molecular Hydrogen Promote Healthful Longevity

Abstract: Age-related diseases represent the largest threat to public health. Aging is a degenerative, systemic, multifactorial and progressive process, coupled with progressive loss of function and eventually leading to high mortality rates. Excessive levels of both pro- and anti-oxidant species qualify as oxidative stress (OS) and result in damage to molecules and cells. OS plays a crucial role in the development of age-related diseases. In fact, damage due to oxidation depends strongly on the inherited or acquired de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 172 publications
0
3
0
Order By: Relevance
“…H 2 has been demonstrated to possess anti-inflammatory, antioxidant, and anti-endoplasmic reticulum (ER) stress properties, and its involvement in the regulation of apoptosis, autophagy, and pyroptosis has been elucidated [12][13][14][15][16][17][18]. In this regard, H 2 can be considered a unique molecule that influences fundamental biological responses.…”
Section: Latest Insights Into H 2 Biology Research-brief Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 has been demonstrated to possess anti-inflammatory, antioxidant, and anti-endoplasmic reticulum (ER) stress properties, and its involvement in the regulation of apoptosis, autophagy, and pyroptosis has been elucidated [12][13][14][15][16][17][18]. In this regard, H 2 can be considered a unique molecule that influences fundamental biological responses.…”
Section: Latest Insights Into H 2 Biology Research-brief Summarymentioning
confidence: 99%
“…In this sense, excessive oxidative stress should be suppressed, but the degree of suppression should be at a level that does not compromise the benefits of reactive oxygen species to the body [15]. To date, while many preclinical studies using H 2 have confirmed organ-protective effects and correction of metabolic abnormalities through its antioxidant and anti-inflammatory effects [12][13][14][15][16][17][18], no severe side effects of H 2 loading have been observed. Therefore, the clinical application of antioxidant therapy with H 2 is considered a realistic challenge.…”
Section: H2 Intervention For Ckd and Hemodialysismentioning
confidence: 99%
“…Longevity, as one of the most complex phenotypes, has intricate and unclear biological mechanisms and is closely associated with GM (Li and Roy 2023 ; Miller et al 2023 ; Coradduzza et al 2023 ; Rahman et al 2023 ). Although omics technologies have advanced the research on GM and longevity, there is still a lack of substantial data support in this field to further validate the microbiota biomarkers associated with longevity (Coradduzza et al 2023 ; Lee et al 2023 ; Miller et al 2023 ; Qiao et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen (H 2 ), which is emerging as a novel therapeutic agent, has demonstrated exceptional antioxidative and anti-inflammatory properties and holds significant promise for treating ROS-related diseases 16 - 18 . Its superior tissue and cell membrane permeability enable effective intratissue diffusion and targeting of organelles, including mitochondria and nuclei—the primary sources of ROS 19 .…”
Section: Introductionmentioning
confidence: 99%
“…H 2 can be instantly delivered to relieve oxidative stress by reacting with and detoxifying highly cytotoxic •OH without disrupting normal metabolic oxidation or cell signaling systems. This ability effectively suppresses inflammation and promotes tissue repair 18 . In addition to its therapeutic potential, hydrogen, as an endogenous inert gas, has been proven to be highly safe and biocompatible when administered through various methods, such as inhalation, drinking, intravenous or intraperitoneal injection, and in situ injection 18 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%